Pictorial essay: Distal colostography - Rahalkar, Mukund D; Rahalkar, Anand M; Phadke, Dilip M (Indian Journal of Radiology and Imaging, 2010)
Distal colostography (DC), also called distal colography or loopography, is an important step in the reparative management of anorectal malformations (ARMs) with imperforate anus, Hirschsprung′s disease (occasionally) and colonic atresia (rarely) in children and obstructive disorders of the distal colon (colitis with stricture, carcinoma or complicated diverticulosis) in adults. It serves to identify/confirm the type of ARM, presence/absence of fistulae, leakage from anastomoses, or patency of the distal colon. We present a pictorial essay of DC in a variety of cases.
Keywords: Imperforate anus; imaging of anorectal malformations; pouch colon